2020
DOI: 10.1111/dar.13026
|View full text |Cite
|
Sign up to set email alerts
|

Investigating possible syndemic relationships between structural and drug use factors, sexual HIV transmission and viral load among men of colour who have sex with men in Los Angeles County

Abstract: Introduction and Aims. Past research investigating syndemic factors and HIV-related outcomes has overlooked the impact of structural conditions on behaviours linked with HIV transmission and disease progression. Given prevalent substance use among our sample, we explored whether four structural conditions indicative of social marginalisation and previously correlated with increased risk for HIV infection demonstrated syndemic (additive/synergistic) effects on: (i) HIV viral suppression; and (ii) self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…25 However, researchers have identified structural factors to be critical in understanding syndemics and their impact on HIV treatment engagement, particularly within communities often left vulnerable to societal forces such as poverty, homelessness, and unemployment. 29,30 Yet only a handful of studies have examined these relations directly. 22 A qualitative study examining HIV treatment engagement among 23 Black men who have sex with men living with HIV (BMSM+) found that poverty, depression, substance use, and intersectional stigma, defined in this study as the overlapping stigmas associated with race, gender, sexual orientation, HIV status, and other marginalized identities, affected HIV treatment engagement decisions of young BMSM+.…”
Section: Psychosocial and Structural Syndemic Factors Related To Hiv ...mentioning
confidence: 99%
See 3 more Smart Citations
“…25 However, researchers have identified structural factors to be critical in understanding syndemics and their impact on HIV treatment engagement, particularly within communities often left vulnerable to societal forces such as poverty, homelessness, and unemployment. 29,30 Yet only a handful of studies have examined these relations directly. 22 A qualitative study examining HIV treatment engagement among 23 Black men who have sex with men living with HIV (BMSM+) found that poverty, depression, substance use, and intersectional stigma, defined in this study as the overlapping stigmas associated with race, gender, sexual orientation, HIV status, and other marginalized identities, affected HIV treatment engagement decisions of young BMSM+.…”
Section: Psychosocial and Structural Syndemic Factors Related To Hiv ...mentioning
confidence: 99%
“…31 Quantitative studies assessing the role of multiple structural factors in treatment behaviors focused on select populations of PLWH, including women of color, 32 young people, 33 injection drug users, 34 and men of color who have sex with men. 30 These studies broadened the examination of syndemics to include previously defined psychosocial factors and structural factors, including unemployment, poverty, incarceration history, housing instability, and HIV stigma. Structural indicators, counted alongside psychosocial factors, were found to be associated with poor ART adherence, detectable viral load, 33,35 and being interrelated, demonstrating a syndemic relationship.…”
Section: Psychosocial and Structural Syndemic Factors Related To Hiv ...mentioning
confidence: 99%
See 2 more Smart Citations
“…7 Moreover, all of these negative and often avoidable health outcomes are associated with experiences of homophobic violence, stigma, discrimination, internalisation of negative assumptions and attitudes about MSM by MSM themselves [8][9][10][11][12] as well as with poverty, unemployment, unstable housing and poor healthcare access. [13][14][15][16] Unfortunately, social factors such as these are often overlooked in the conventional frameworks of comorbidity and multimorbidity 17 even though our understanding of diseases clustering demonstrates the need to incorporate social and environmental elements. 18 To offer meaningful improvements to the health of marginalised populations, public health researchers and clinicians must move beyond a reductionist understanding of disease causation to more complex models of diseases interaction taking into account the social forces driving health inequalities.…”
Section: Introduction Backgroundmentioning
confidence: 99%